(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2005)
The views of a sympathetic but critical outsider to existential therapy are outlined. An alternative explanation for human alienation is briefly considered. The loss of transparency in contemporary discourse is lamented and some examples from my own life are given. Connections between one’s worldview and possible underlying pathology are explored.